Research recast(ed): S2E1 - Research at #MacEwanU with President and Vice-Chancellor Dr. Annette Trimbee - Ekelund, Brittany; Cave, Dylan; Trimbee, Annette (My University, 2022)
Today we sit down with Dr. Annette Trimbee to explore what MacEwan has in store going into the next year. It’s all about MacEwan’s Strategic Vision. We touch on teaching greatness, supporting students and being supported by students, as well as ideas on how to continue building community connections and pursuing exciting new projects in the heart of Edmonton.
Keywords: MacEwan University; strategic vision; student support; building community